Isolated Cardiac Metastasis from Colorectal Cancer in a 35-Year-Old Man - Jacopo Pizzicannella; Vincenzo Ricci; Riccardo Gorla; Elena Spinapolice; Antonio Esposito (Case Reports in Medicine)
We present the case of a 35-year-old patient who was found to be affected by an isolated clinically silent cardiac metastasis despite a negative CT follow-up at one year from abdominal surgery for colorectal cancer. CT/PET and tumor marker GICA were fundamental in suggesting the diagnosis, which was then confirmed by cardiac magnetic resonance and surgical biopsy. This is a very rare modality of presentation of cardiac metastasis because of the young age of our patient and the absence of disease in other sites.